The need for an MLIS distance program in Western Visayas - Malte, Cristina C. (2002)
This research aimed at determining the need for an MLIS program in the distance mode in Western Visayas. It focused on the profile of the 153 randomly selected librarians in the region, specifically their age group, school employer, length of service as librarians, bachelor's degree obtained, and master's units earned. The study, likewise was concerned with the librarians' desire to earn the MLIS degree, their willingness to enroll in distance MLIS program, their need for the MLIS degree, the seriousness of their reasons for failing to earn the MLIS degree, the perceived benefits for earning the MLIS degree, and the advantages and the disadvantages of the MLIS distance program.